2020
DOI: 10.3389/fendo.2020.00519
|View full text |Cite
|
Sign up to set email alerts
|

Metformin May Contribute to Inter-individual Variability for Glycemic Responses to Exercise

Abstract: Metformin and exercise independently improve glycemic control. Metformin traditionally is considered to reduce hepatic glucose production, while exercise training is thought to stimulate skeletal muscle glucose disposal. Collectively, combining treatments would lead to the anticipation for additive glucose regulatory effects. Herein, we discuss recent literature suggesting that metformin may inhibit, enhance or have no effect on exercise mediated benefits toward glucose regulation, with particular emphasis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 131 publications
(198 reference statements)
1
13
0
Order By: Relevance
“…There is inter-individual variability in the metabolic responses to physical training [ 76 ]. Different factors, such as genetic and epigenetic features, nutrition, concomitant treatments, may explain this heterogeneity [ 77 , 78 ]. Gut microbiota composition also may be a potential factor to explain the training response variability [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is inter-individual variability in the metabolic responses to physical training [ 76 ]. Different factors, such as genetic and epigenetic features, nutrition, concomitant treatments, may explain this heterogeneity [ 77 , 78 ]. Gut microbiota composition also may be a potential factor to explain the training response variability [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…All subjects were treated with metformin. Studies have shown that metformin may blunt effects of exercise training on insulin sensitivity improvements and contribute to inter-individual variability for glycemic responses to exercise ( 55 , 56 ). Moreover, metformin abrogates the exercise‐mediated increase in skeletal muscle mitochondrial respiration ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, exercise can increase glucose uptake independent of PI3 kinase activity [10][11][12]. The second pathway involves an insulin-independent signaling system, which is thought to have greater translational relevance for diabetes management [13,14]. When muscles repeat contractions and relaxation during exercise, improvements in insulin sensitivity and glucose tolerance are stimulated [15,16].…”
Section: Introductionmentioning
confidence: 99%